Opportunities and Limitations of Urban Agendas as Tools for Sustainable Management of Urban University Campuses - Guillermo Rodrigo-Torromé; José M. Coronado; Rita Ruiz; Inmaculada Gallego (Land)
Despite the fact that university campuses have great potential to contribute significantly to urban sustainability, to date, no strategic sustainability plans in this context have been part of any urban agenda, even though these can constitute an adequate framework for such plans. The aim of this paper is to define a procedure for adapting the strategic framework of a national urban agenda, in this case, the Spanish one, to the context of a university, and to discuss the possible limitations and opportunities of this approach. For this purpose, both the strategic framework of the Spanish Urban Agenda (i.e., the strategic and specific objectives and their lines of action) and its sets of indicators (i.e., indicators for the evaluation and monitoring of the objectives and descriptive data) are transferred to the academic context. This procedure makes it possible to obtain a “university urban agenda” with a simplified strategic framework and indicators that are appropriate to the context of universities and that facilitate the collaboration and participation of different agents of the university community to achieve campus management in accordance with the principles of sustainable development.